Effect of salts addition of some organic acids on growth performance of Common Carp Juvenile Cyprinus carpio L.: Ashwaq Muhan Muhsan and Saeed Abdulsaddah Al-Shawi - Muhsan, Ashwaq Muhan (The Iraqi Journal of Veterinary Medicine, 2017)
This study was carried out in the laboratories of fish for 90 days in 16 glass aquaria (60 cm, 40 cm and 30 cm/70 L) to investigate the effect of some organic acids salts on some growth indices of common carp fish Cyprinus carpio L. A 128 fish were used with an average weight of (40.8±1) gm. and have been distributed on eight treatments with two replicate and eight fish for each replicate. Formulated eight diets that equally iso-nitrogenous (33.85%) and iso-caloric (1535.605 KJ/gm) were investigated. Organic acids salts (Sodium lactate, Sodium acetate and Sodiumformate) were supplemented singly (0.5% of each salts) and mixed to the experimental diets (0.25% of each salts). The statistical results showed that treatments T6 (0.25% sodium lactate + 0.25% sodium formate) had the best studied growth parameters at the level of P≤0.05 which clarified by weight gain (41.05±0.25 gm) and food conversion ratio (2.8±0.02).